THE CORRELATION BETWEEN READING MOTIVATION AND READING COMPREHENSION OF THE FIRST YEAR STUDENTS OF SMK TARUNA SATRIAPEKANBARU - Ima Hartati; Erni '; Syafri K ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was designed to describe the significant of the correlation between reading motivation and reading comprehension. The aim was to find out the correlation between students’ reading motivation and students’ reading comprehension. This Correlation research took place in SMK Taruna Satria Pekanbaru in July 2015. The sample was 36 students from First Year students that took by using cluster random sampling. In collecting the data, there were 30 questions that included in this test. The duration time for doing the test was 90 minutes. The data was analyzed by calculating the students’ score in reading motivation, finding out the reading comprehension score and correlating the two variables. The students’ score classified into three level of students’ reading motivation; they are: Low, Moderate, and High. Besides, the students’ score classified into five level mastery of Reading Comprehension; they are: very poor, poor, mediocre, good, and excellent. The data was presented by using graphic. Based on the result finding of this research, the coefficient correlation ( obtained was 0,424. Therefore, it answered the research that there was a relationship between reading motivation and reading comprehension in moderate level. For more details, the correlation of intrinsic motivation and reading comprehension is significant in 0,016 by the coefficient correlation 0,399 that considered as low correlation. In another side, the correlation of extrinsic motivation and reading comprehension is significant in 0,000 by the coefficient correlation 0,599 that considered as moderate correlation. It can be concluded that based on the data that was analyzed, the students reading extrinsic motivation influence the students’ comprehension more than the intrinsic motivation. In other words, the contribution of reading motivation towards reading comprehension significant enough for the first year students of SMK Taruna Satria Pekanbaru. Another result from the students perception about the teacher’s teaching method as extrinsic motivation factor found out that they are more motivated if the teacher teaches them by speech as one of the stages of inquiry based learning than teacher teaching by group discussion and questioning. Keywords: Correlation, Reading Motivation, Reading Comprehension